2018
DOI: 10.1017/s0007114518002015
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory and determinants of change in lean soft tissue over the postpartum period

Abstract: The aim of this study was to characterise changes in lean soft tissue (LST) and examine the contributions of energy intake, physical activity and breast-feeding practices to LST changes at 3 and 9 months postpartum. We examined current weight, LST (via dual-energy X-ray absorptiometry), dietary intake (3-d food diary), physical activity (Baecke questionnaire) and breast-feeding practices (3-d breast-feeding diary) in forty-nine women aged 32·9 (sd 3·8) years. Changes in LST varied from -2·51 to +2·50 kg with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(50 reference statements)
0
3
1
Order By: Relevance
“…Lean mass is associated with many health benefits, including increased metabolic rate, reduction in inflammatory markers, and increased BMD. 10 58 In our cohort, we found no relationship between breastfeeding and BMD at 1 year postpartum. Breastfeeding has been shown to reduce BMD, particularly within the first 6 months postpartum, but most studies show a full bone mass recovery afterwards.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Lean mass is associated with many health benefits, including increased metabolic rate, reduction in inflammatory markers, and increased BMD. 10 58 In our cohort, we found no relationship between breastfeeding and BMD at 1 year postpartum. Breastfeeding has been shown to reduce BMD, particularly within the first 6 months postpartum, but most studies show a full bone mass recovery afterwards.…”
Section: Discussioncontrasting
confidence: 60%
“…There are conflicting data regarding its effect on body composition and BMD in the general population. [8][9][10][11][12][13] While an intervention to promote breastfeeding duration did not result in lower percentage of body fat in a large cluster-randomized trial, 14 one cohort study showed a beneficial association between breastfeeding and fat mass index (FMI) in women having had a child in the last 5 years 9 and two prospective studies suggested that exclusive breast feeding was associated with lower fat mass than mixed breastfeeding. 15 16 In addition, breastfeeding has been associated with a lower visceral adipose tissue in some studies.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it is possible to ascribe the increase in body mass by a significantly high lean mass (P<0.05) in FO group vs. C group. However, it is possible to associate postpartum period with lean mass loss in humans as it depends on factors, such as exercise, lactation and diet [27,28]. A low amount of lean mass can contribute to an increase in body fat and obesity due to the decrease in energy metabolism.…”
Section: Resultsmentioning
confidence: 99%